(3TQM CfehPLs - (3GdCQOHjdj GdQhej, LeGd GdOjf, Zfj RGOg, eMeO Hf YHO GdZfj, J (B647 (3g`s
(3ChdgG (B:s
(3HSe Gddg(B...(3GdMeO ddg GdPj LYd GdYQHjI eaJGM GdHjGf(B...(3hHYO jbhd GdabjQ Gdehdi(B...(3eMeO Hf YHO GdZfj(B...(3deG QCjJ eNJUQ GdEeGe(B...(3LGQ Gddg(B...(3CYfj CfehPL aj GdfMh bdjd GddaX(B...s
(3BNQgG (B:s
...(3hMQha GdJPcjQ eOI JVGa Ydi BNQ cd cdeI jba GdeJcde YdjgG dJPcjQ eG jJcde Hg HYOgG eKd Cf jbhd GdQLd aj fMh bGd hjbhd hef bGdG hjbhdGs
(3CJe JCdjag aj (B18 (3TYHGf (B1257(3g`s
(3JHUQI GdeDda (B:s
(3CnqQN cMGdI dhaGJg (B: 1036(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B6(3,U(B211s
(3eYLe GdeDdajf(B:(3L(B3(3,U(B417s
Keywords: (3GdfMhs